Un modelo de Credit Scoring para instituciones de microfinanzas en el marco de Basilea II - Rayo Cantón, Salvador (2010)
The growth of microcredit worldwide along with international rules on capital requirements (Basel II) are increasing the competition between microfinance institutions (MFIs) and banks for this business segment. The bank system traditionally has relied on adequate credit scoring models to analyze the risk of payment failures, but this has not been the case in supervised MFIs. The objective of this research is to design a credit scoring model for any institution subjected to supervision and specialized in microcredit as the Development Agency for Small and Micro Enterprise (Entidad de Desarrollo de la Pequeña y Micro Empresa - Edpyme) of the financial system in Peru. The results of this research includes a methodology and the steps needed to design the model, and the assessment and validation process that can be applied in the business area, in particular, to establish an interest rate policy with customers. Eventually, the paper also explains how the model can be used to develop credit risk management under the Basel II IRB approaches.